공정부산물의 방사선적 특성과 처분방안에 관한 기본 연구 - 정종태(JONG TAE JEONG), 백민훈(Minhoon Baik), 박정균(CHUNG KYUN PARK), 박태진(Tae-Jin Park), 고낙열(Nak-Youl Ko), 윤기훈(KIHOON YOON) (Journal of nuclear fuel cycle and waste technology (Online), 2014)
생활주변방사선안전관리법 도입에 따라 재활용하지 못하는 공정부산물의 안전관리를 위해서는 방사선적 안전성 확보가 필 수적이다. 이를 위해서 처분대상 공정부산물 특성화 자료 수집 및 분석, 처분방법과 처분시설의 조사 및 분석, 처분시설의 운 영으로 인한 방사선적 안전성평가 방법론 정립과 도구 확보, 주요 입력자료들의 안전성에 미치는 영향 파악 등이 필요하다. 이를 통하여 매립과 같은 참조 처분방법을 선정하고 피폭선량과 인체보건 리스크 평가를 통하여 공정부산물 처분에 따른 방 사선적 안전성 확보를 위한 절차 및 기준마련을 위한 기술적 근거를 확보할 필요가 있다. 본 연구에서는 공정부산물 처분방 법과 공정부산물 처분시설에 대한 국내외 현황 조사 및 분석과 국내외 주요 산업별 처분대상 공정부산물 특성화 자료 수집 및 분석을 수행하였다. 이를 바탕으로 주요 공정부산물 특성에 따른 관리방안과 매립 처분시설에 대한 개념설계를 제안하였 다. 또한, 공정부산물 처분시 대기확산에 의한 방사성핵종의 전이경로와 침출수 유출로 인한 방사성핵종의 전이경로 파악을 수행하고 적절한 코드를 선정하여 예제 평가를 수행함으로써 코드의 유용성을 확인하였다. 그리고 국내 대표 공정부산물인 비산재, 인산석고, 레드머드 특성화 자료를 이용하여 공정부산물 처분시 피폭선량 및 초과 암 리스크를 평가하고 분석하였 다. 개념적 설계 예제에 대한 방사선적 안전성 평가 결과에 의하면 공정부산물 처분시 피폭선량 및 초과 암 리스크는 매우 낮 은 값을 가지며 우려할 만한 방사선적 영향을 보이지는 않는다. 연구결과는 향후 생활방사선 안전관리를 위한 규제기술 개 발에 활용 가능할 뿐만 아니라 생활주변방사선안전관리법 이행기술 기반 구축에 기여할 수 있을 것이다. Securing the radiological safety is a prerequisite for the safe management of the naturally occurring radioactive materials (NORM) which cannot be reused. This becomes a crucial focus of our R&D efforts upon the implementation of the Act on Protective Action Guidelines against Radiation in the Natural Environment. To secure the safety, the establishment of technical bases and procedures for securing radiological safety related to the disposal of NORM is required. Thus, it is necessary to analyze the characteristics, to collect the data, to have the radiological safety assessment methodologies and tools, to investigate disposal methods and facilities, and to study the effects of the input data on the safety for the NORM wastes. Here, we assess the environmental impact of the NORM waste disposal with respect to the major domestic and foreign NORM characteristics. The data associated with major industries are collected/analyzed and the status of disposal facilities and methodologies relevant to the NORM wastes is investigated. We also suggest the conceptual design concept of a landfill disposal facility and the management plan with respect to the major NORM wastes characteristics. The radionuclide pathways are identified for the atmospheric transport and leachate release and the environmental impact assessment methodology for the NORM waste disposal is established using a relevant code. The assessment and analysis on the exposure doses and excessive cancer risks for the NORM waste disposal are performed using the characteristics of the representative domestic NORM wastes including flying ash, phosphor gypsum, and redmud. The results show that the exposure dose and the excessive cancer risks are very low to consider any radiation effects. This study will contribute to development in the areas of the regulatory technology for securing radiological safety relevant to NORM waste disposal and to the implementation technology for the Act.